SUPPORT OF TEACHING ALGORITHMIZATION WITH IT TOOLS - JELÍNEK, Jiří (Trends in education, 2016)
The level of students' abilities to create algorithms for all sorts of tasks continues to decrease. We may discuss the extent of teaching this topic in different types and levels of schools. However, from the perspective of a teacher is more important to ensure and set support of teaching with tools that could be used to improve its overall efficiency. On this topic is focused also this paper, in which, after introduction into the problem, we identify major categories of support tools defined by the presentation of algorithms. These categories we will then try to compare from the point of view of their use for teaching algorithms for the target group of beginners without other special knowledge applicable in a given topic. Some specific instruments representing the different categories and the results of comparison will be presented too.
Keywords: education support; algorithmization; algorithms; information technology.